Computer aided learning environment for biology / Foong Pek Hin - Foong , Pek Hin (2001)
Traditional learning on biology requires of memory rather than understanding. As better educational technology emerges, we are able to utilise the computer as an important tool in learning. Many educational and pedagogical issues, particularly in the field or Artificial intelligence are looked at to help consider a good design for a computer learning tool. Existing computer aided learning materials are also studied to pinpoint their better features and incorporate them into the learning tool. A learning tool is proposed for effective learning in relating facts, rules, text and graphics. This system will have a Study Section containing notes that incorporates multimedia features to enhance motivation and interest of students. Apart from that, it will have an intelligent Database Section where students are given the opportunity to improve and test their knowledge. Not only that, this section will see the interaction of students with the program as they are allowed to add and remove information from the program. This learning tool would be developed following the Rapid Application Development (RAD) methodology. It will be programmed using Visual Prolog 5.1. The use or Visual Prolog 5.1 will help to make a presentable GUI as well a an intelligent system. As for the s stem requirements of the finished product, it would be able to run on a stand-alone computer with a CD-ROM/floppy drive and a generic hard disk.